Existence of Quasilinear Neutral Impulsive Delay Integrodierential Equations - Prabakarn, R (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
In this paper, we prove the existence of solutions for a quasilinear neutral impulsive delay integrodierential equations with nonlocal conditions. The results are obtained by using semigroup theory and the Monch's xed point theorem. An example is provided to illustrate the theory.An application of the same problem is discussed. Key Words: Existence, neutral dierential equation, impulsive dierential equation,measure of noncompactness, xed point theorem. 2000 AMS Subject Classication: 34A37, 47D06, 47H10, 74H20, 34K40.